2022
DOI: 10.1038/s41598-022-20858-5
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis-related lncRNA signature predicts prognosis and immune response for cervical squamous cell carcinoma and endocervical adenocarcinomas

Abstract: Necroptosis, a programmed form of necrotic cell death, plays critical regulatory roles in the progression and metastatic spread of cancers such as cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC). However, there are few articles systematically analyzing the necroptosis-related long non-coding RNAs (NRlncRNAs) correlated with CESC patients. Both RNA-sequencing and clinical data of CESC patients are downloaded from TCGA database in this study. Pearson correlation analysis, least absolute s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Previous studies had demonstrated that lncRNA MIR100HG was identified as an oncogene in various cancers, including breast cancer (Chen et al, 2020), hepatocellular carcinoma (HCC) (Li et al, 2021), gastric Frontiers in Genetics frontiersin.org cancer (Li J. et al, 2019;Li et al, 2020), and colorectal cancer (Li W. et al, 2019). However, studies in MIR100HG also proved that it could exert tumor suppressive effects in papillary-thyroid carcinoma (Yang et al, 2021;Park and Lee, 2022) and cervical cancer (Lang et al, 2022;Lin et al, 2022). Furthermore, there are opposing results about the role of lncRNA MIR100HG in bladder cancer (BC).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had demonstrated that lncRNA MIR100HG was identified as an oncogene in various cancers, including breast cancer (Chen et al, 2020), hepatocellular carcinoma (HCC) (Li et al, 2021), gastric Frontiers in Genetics frontiersin.org cancer (Li J. et al, 2019;Li et al, 2020), and colorectal cancer (Li W. et al, 2019). However, studies in MIR100HG also proved that it could exert tumor suppressive effects in papillary-thyroid carcinoma (Yang et al, 2021;Park and Lee, 2022) and cervical cancer (Lang et al, 2022;Lin et al, 2022). Furthermore, there are opposing results about the role of lncRNA MIR100HG in bladder cancer (BC).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis employed GSEA software version 4.1.0 to investigate gene function. The MSIGDB database from the GSEA website (http://software.broadinstitute.org/gsea/msigdb) was applied for this purpose 18–20 . In order to identify the pathways that exhibit the greatest differences across subgroups, we employed the technique of differential gene induction to rank them.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, a Univariate Cox analysis was performed on the necroptosis-related gene signature in the train group to identify prognosis-related genes (p < 0.05) 15 , 16 . Then, the optimal Log(λ) value was determined using LASSO regression analysis with tenfold cross-validation 17 22 , and a gene signature was constructed accordingly 23 , 24 . To validate our signature, the entire group was utilized in order to confirm the prognostic signature.…”
Section: Methodsmentioning
confidence: 99%